Archaeology's visual culture : digging and desire - Balm, Roger, 1947- (Milton Park, Abingdon, Oxon : Routledge, 2016)
'Archaeology's Visual Culture explores archaeology through the lens of visual culture theory. The insistent visuality of archaeology is a key stimulus for the imaginative and creative interpretation of our encounters with the past, acknowledging the multiplicity of meanings that cohere around artifacts, archaeological sites and museum displays. Archaeology's Visual Culture investigates the nature of this projection, revealing an embedded subjectivity in the imagery of archaeology. Using a wide range of case studies the book highlights the way archaeologists view objects and the consequences that ensue from ways of seeing'--Provided by publisher.
Insistent visuality -- Scopic privilege and appropriation -- Stratigraphy -- Imagination and the ruin -- Aerial archaeology and its haunting -- Remote sensing and rocket visions -- Wither the object?
Includes bibliographical references.
Keywords: Archaeology -- Philosophy -- Case studies; Archaeology -- Psychological aspects -- Case studies; Archaeologists -- Psychology -- Case studies; Visual perception -- Case studies; Visual communication -- Case studies; Antiquities -- Collection and preservation -- Case studies; Excavations (Archaeology) -- Case studies; Archaeological museums and collections -- Case studies